2018
DOI: 10.3389/fnhum.2018.00371
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Pattern of the Hemodynamic Response as Measured by Functional Near-Infrared Spectroscopy (fNIRS) Studies in Newborns, Less Than a Month Old: A Systematic Review

Abstract: It has been 20 years since functional near-infrared spectroscopy (fNIRS) was first used to investigate the evoked hemodynamic response to a stimulus in newborns. The hemodynamic response to functional activation is well-established in adults, with an observed increase in concentration change of oxygenated hemoglobin (Δ[HbO2]) and decrease in deoxygenated hemoglobin (Δ[HHb]). However, functional studies in newborns have revealed a mixed response, particularly with Δ[HHb] where an inconsistent change in directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 97 publications
(202 reference statements)
2
39
0
Order By: Relevance
“…46 In a recently published review investigating the pattern of the HR in fNIRS studies in term newborns less than 1 month old, the authors came to the conclusion that the typical response in newborns is not well established. 2 The majority of papers identified for this review reported an increase in Δ½O 2 Hb, with only some of them reporting a decrease in Δ½HHb. Furthermore, they did not observe a clear association between the reported response and stimulus type.…”
Section: Can a Typical Stimulus-evoked Hemodynamic Response Be Definementioning
confidence: 94%
See 3 more Smart Citations
“…46 In a recently published review investigating the pattern of the HR in fNIRS studies in term newborns less than 1 month old, the authors came to the conclusion that the typical response in newborns is not well established. 2 The majority of papers identified for this review reported an increase in Δ½O 2 Hb, with only some of them reporting a decrease in Δ½HHb. Furthermore, they did not observe a clear association between the reported response and stimulus type.…”
Section: Can a Typical Stimulus-evoked Hemodynamic Response Be Definementioning
confidence: 94%
“…Neuroimaging with fNIRS has the potential to provide insights into the origin of neonatal brain lesions, as well as into functional development of both the normal and the abnormal brain. 2,3 The ability of fNIRS to access neurovascular coupling associated with neuronal activity offers a useful opportunity to investigate, for example, the neural basis of visual cognitive development in infants. This is of special interest in preterm-born infants, as many of them develop visual cognitive impairment in later childhood.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aasted [40] Statistical analysis of fNIRS data 2014 Tak [41] Pattern of hemodynamic response in newborn < 1 month 2018 de Roever [42] Pattern of hemodynamic response in infants 2018 Issard [43] Integration of fNIRS with: The advantages and disadvantages of fNIRS have been widely reported in several recent review articles [5,47,48]. Unlike other neuroimaging modalities, fNIRS has a very high experimental flexibility.…”
Section: Where Do We Standmentioning
confidence: 99%